Association and performance of polygenic risk scores for breast cancer among French women presenting or not a familial predisposition to the disease. (January 2023) - Jiao, Yue; Truong, Thérèse; Eon-Marchais, Séverine; Mebirouk, Noura; Caputo, Sandrine M.; Dondon, Marie-Gabrielle; Karimi, Mojgan; Le Gal, Dorothée; Beauvallet, Juana; Le Floch, Édith; Dandine-Roulland, Claire; Bacq-Daian, Delphine; et al.
Abstract: Background: Three partially overlapping breast cancer polygenic risk scores (PRS) comprising 77, 179 and 313 SNPs have been proposed for European-ancestry women by the Breast Cancer Association Consortium (BCAC) for improving risk prediction in the general population. However, the effect of these SNPs may vary from one country to another and within a country because of other factors. Objective: To assess their associated risk and predictive performance in French women from (1) the CECILE population-based case-control study, (2) BRCA1 or BRCA2 ( BRCA1/2 ) pathogenic variant (PV) carriers from the GEMO study, and (3) familial breast cancer cases with no BRCA1 /2 PV and unrelated controls from the GENESIS study. Results: All three PRS were associated with breast cancer in all studies, with odds ratios per standard deviation varying from 1.7 to 2.0 in CECILE and GENESIS, and hazard ratios varying from 1.1 to 1.4 in GEMO. The predictive performance of PRS313 in CECILE was similar to that reported in BCAC but lower than that in GENESIS (area under the receiver operating characteristic curve (AUC) = 0.67 and 0.75, respectively). PRS were less performant in BRCA2 and BRCA1 PV carriers (AUC = 0.58 and 0.54 respectively). Conclusion: Our results are in line with previous validation studies in the general population and in BRCA1/2 PV carriers. Additionally, we showed that PRS may be of clinical utility for women with a strong family history of breast cancer and no BRCA1/2 PV, and for those carrying a predicted PV in a moderate-risk gene like ATM, CHEK2 or PALB2 . Highlights: Three polygenic risk scores for breast cancer assessed in 3 groups of French women. All of them associated with breast cancer but effects varied depending on group. Predictive ability is higher in women with no BRCA1 or BRCA2 pathogenic variant. Opportunity to refine risk stratification in carriers of a moderate-risk variant. Effects of SNPs in polygenic risk scores vary depending on country and population.